Julius the Perfectly Pesky Pet Parrot - Wiggins, Veralee; Nang Chan Yeema (Nampa, Idaho, United States Pacific Press Publishing Association, 1958)
With the help of his pet parrot, Mitch makes some important discoveries about friendship, responsibility, and love.
Keywords: Adult Fiction